Efficacy of PSMA PET-Guided Radiotherapy for Oligometastatic Castrate-Resistant Prostate Cancer - Henkenberens, Christoph; Derlin, Thorsten; Bengel, Frank; Ross, Tobias L.; Kuczyk, Markus A.; Giordano, Frank A.; Sarria, Gustavo R.; Schmeel, Leonard Christopher; Christiansen, Hans; von Klot, Christoph A. J. (Frontiers in Oncology, 2021)
Purpose: To assess the outcome of radiotherapy (RT) to all PSMA ligand positive metastases for patients with castrate-resistant prostate cancer (mCRPC). Patients and methods: A total of 42 patients developed oligometastatic mCRPC and received PSMA PET-guided RT of all metastases. The main outcome parameters were biochemical progression-free survival (bPFS), and second-line systemic treatment free survival (SST-FS). Results: A total of 141 PSMA ligand-positive metastases were irradiated. The median follow-up time was 39.0 months (12-58 months). During the follow-up five out of 42 (11.9%) patients died of progressive mPCa. Five out of 42 (11.9%) patients showed no biochemical responses and presented with a PSA level ≥10% of the baseline PSA at first PSA level measurement after RT and were classified as non-responders. The median PSA level before RT was 4.79 ng/mL (range, 0.4-46.1), which decreased significantly to a median PSA nadir level of 0.39 ng/mL (range, <0.07-32.8; p=0.002). The median PSA level at biochemical progression after PSMA ligand-based RT was 2.75 ng/mL (range, 0.27-53.0; p=0.24) and was not significantly different (p=0.29) from the median PSA level (4.79 ng/mL, range, 0.4-46.1) before the PSMA ligand-based RT. The median bPFS was 12.0 months after PSMA ligand PET-based RT (95% CI, 11.2-15.8) and the median SST-FS was 15.0 months (95% CI, 14.0-21.5). Conclusion: In well-informed and closely followed-up patients, PSMA PET-guided RT represents a viable treatment option for patients with oligometastatic mCRPC to delay further systemic therapies.